2011
DOI: 10.1063/1.3666226
|View full text |Cite
|
Sign up to set email alerts
|

Point defect engineering strategies to suppress A-center formation in silicon

Abstract: We investigate the impact of tin doping on the formation of vacancy-oxygen pairs (VO or A-centers) and their conversion to VO 2 clusters in electron-irradiated silicon. The experimental results are consistent with previous reports that Sn doping suppresses the formation of the A-center. We introduce a model to account for the observed differences under both Sn-poor and Sn-rich doping conditions. Using density functional theory calculations, we propose point defect engineering strategies to reduce the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 19 publications
4
71
0
Order By: Relevance
“…It is therefore Sn doping and the formation of SnVO complexes that is ideal for the suppression of A-centres in Si, due to the strong binding and the fact that Sn is more soluble in Si than Pb. Recent studies 10 have determined that Sn can be incorporated in Si in concentrations up to near 10 19 cm -3 without the formation of precipitates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore Sn doping and the formation of SnVO complexes that is ideal for the suppression of A-centres in Si, due to the strong binding and the fact that Sn is more soluble in Si than Pb. Recent studies 10 have determined that Sn can be incorporated in Si in concentrations up to near 10 19 cm -3 without the formation of precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a recent study an increased concentration of Sn was used to suppress the formation of the deleterious A-centres by the formation of SnVO defects. 10 This was justified through binding energy arguments as the oversized isovalent atoms benefit from the space provided by the A-centre voids, so that the lattice atoms surrounding them relax. The high binding energies ensure that the A-centres are anchored to the isovalent atoms, forming DVO defects (D = Ge, Sn, and Pb), and thus cannot diffuse to form larger members of the V n O m family (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silicon, isovalent codoping has been recently used to defect engineer the formation and stability of the oxygen-vacancy pair (or A-center). 26 These issues are presently under investigation from the viewpoint of the cluster formation model as the isovalent codopants of interest have significantly different electronegativities (hafnium 1.3 to lead 2.33) offering possibilities for tuning the properties. Another way forward is to consider alloy group-IV semiconductors such as the Si 1 À x À y Ge x Sn y alloys (i.e., change the electronegativity of the host atoms around the dopant).…”
Section: -mentioning
confidence: 99%
“…The introduction of dopants in the lattice can lead to local strains that can in turn impact the defect processes of a material [27][28][29][30][31][32][33]. In previous investigations it was shown that the introduction of large isovalent dopants such as Sn can impact dopant-defect interactions in Ge (and in Si) [12,19].…”
Section: Introductionmentioning
confidence: 99%